Secure Dominance in Neutrosophic Graphs - Sivasankar S.; Said Broumi (Neutrosophic Sets and Systems, 2023)
Secure dominance is a significant proportion of dominance which plays vital role in communication networks. In this article, we present and analyze an idea of the secured neutrosophic dominance and totally neutrosophic dominance number of neutrosophic graphs primarily based on strong arcs and the properties of both notions are studied. The terms 2- neutrosophic dominance number, 2- secured neutrosophic dominance variety, 2- totally neutrosophic dominance, and 2- secured neutrosophic dominance number also are defined. Some of their theoretical properties are investigated.